A Mayer-Rokitansky-Kuster-Hauser Syndrome in a Neonate: A Case Report - Nasrin Khalesi; Mandana Kashaki; Nastaran Khosravi; Zahra Vahedi; Mona Alinejad-Naeini (Iranian Journal of Neonatology, 2025)
Background: Mayer-Rokitansky-Kuster-Hauser (MRKH) syndrome is defined as the congenital incomplete development of Müllerian structures in women who otherwise have the phenotype with a normal karyotype (46, XX), normal external genitalia, and functional ovaries. We present the case of a neonate admitted with features of MRKH syndrome.Case Report: We present a female neonate with a gestational age of 37 weeks and two days with a birth weight of 2650 grams who was admitted to the hospital. Fistulography radiology was performed for the baby in such a way that water-soluble contrast material was used. The baby was discharged with good general condition, normal tests, and stable hemodynamics vesicostomy.Conclusion: MRKH syndrome is a very heterogeneous phenotypic and genetic disorder. Although more information is still needed about the etiology and management of MRKH, progress has been made in the past decades regarding efficient diagnostic methods and appropriate medical management.